If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-8m+8-5(m-3)=3m-(6m-2)-7m+9
We move all terms to the left:
-8m+8-5(m-3)-(3m-(6m-2)-7m+9)=0
We multiply parentheses
-8m-5m-(3m-(6m-2)-7m+9)+15+8=0
We calculate terms in parentheses: -(3m-(6m-2)-7m+9), so:We add all the numbers together, and all the variables
3m-(6m-2)-7m+9
We add all the numbers together, and all the variables
-4m-(6m-2)+9
We get rid of parentheses
-4m-6m+2+9
We add all the numbers together, and all the variables
-10m+11
Back to the equation:
-(-10m+11)
-13m-(-10m+11)+23=0
We get rid of parentheses
-13m+10m-11+23=0
We add all the numbers together, and all the variables
-3m+12=0
We move all terms containing m to the left, all other terms to the right
-3m=-12
m=-12/-3
m=+4
| x+3x+1.5+180=455 | | -10x-3=77 | | 2=11/4k-3 | | (x+15)+(5x+57)=90 | | 5=30^x | | 65=32(2y+8) | | 1.5y-7=O.5y | | 2x–7=-11 | | 7c-16=26-5c | | 4(x-3)=8(x+4 | | 1/2+4=1/8b+88 | | -9p-3(6-6p)=6(p-2)-21 | | X^-4x=0 | | (5/x)+5/(x+10)=4/3 | | (6x+59)=(3x-14) | | 170=50+0.15x | | 2(8s+8)-10s=3(2s+6)-20 | | 12x+2=-12x+26 | | (5/x)+(5/(x+10))=4/3 | | M=b/8 | | 9p-17=48+4p | | 8-(2a+5)=8-2a+5 | | 12/20x=-36/44 | | -16/19x=-20/38 | | X=54+1/6x | | n/5+0.6=2 | | 15x+75=85 | | 0.90x+0.05(14-x)=0.10(24) | | -1/8x=-2/7 | | 5n+0.6=2 | | 180=45°+2k°+k° | | 210+.15m=324 |